Designing effective Si/Ag interface via controlled chemical etching for photoelectrochemical CO2 reduction. Issue 44 (3rd August 2018) - Hu, Yongpan; Chen, Fengjiao; Ding, Pan; Yang, Hui; Chen, Junmei; Zha, Chenyang; Li, Yanguang
Abstract : Controlled chemical etching of Si wafer by Ag + ions results in the effective Si/Ag interface for photoelectrochemical CO2 reduction to CO. Abstract : Photoelectrochemical reduction of CO2 to value-added chemicals represents a promising approach for artificial photosynthesis, but often suffers from limited selectivity and stability. Improving its performance would require proper design of semiconductor and co-catalyst materials, along with a strategy for effective coupling. Here, we report that controlled chemical etching of Si wafer by Ag + ions yields effective semiconductor/co-catalyst interface for photoelectrochemical CO2 reduction. Resultant photocathodes exhibit large photocurrent density (∼10 mA cm −2 under 0.5 sun), great CO faradaic efficiency (90% at −0.5 V versus reversible hydrogen electrode), and impressive operational stability (little activity or selectivity loss within 8 h). Further enhancement (by ∼20%) of photocurrent density is achieved by combining photolithography patterning with chemical etching. Our study applies long-known chemistry as an unexpected solution and may provide a new strategy for high-performance photoelectrochemical CO2 reduction.